Truth Claims Across Media - Schirrmacher, Beate; Mousavi, Nafiseh (Palgrave Studies in Intermediality,, 2024)
This open access book offers an intermedial approach to truthful communication. Bringing together a wide range of media types and interactions from a transmedial perspective, the volume maps out how truth claims are made in different contexts, and how different media promise to create a truthful perception of the social world. The flexible communicative possibilities of digital technology have a significant impact on our perception of truth and truthfulness of communication. Bot accounts, deep fake videos, or AI technology draw attention to how reliable communication is destabilized and questioned. In this unstable climate, binaries such as true/false, authentic/fake and fiction/facts are difficult to apply. Instead, it is crucial to investigate how media products construct truthfulness in different ways. The volume brings together various media types and contexts such as press conferences, documentaries and mockumentaries, images in magazines and on social media, horror movies, biopics, and educational games and explores how truth claims, authenticity discourses, and knowledge communication are established and how they collide, merge, or are confused. Beate Schirrmacher is an Associate Professor in Comparative Literature at Linnaeus University, Sweden. She is the head of the International Society of Intermedial Studies, and the co-editor of Intermedial Studies: An Introduction to Meaning across Media. Her research focuses on truth claims and narratives in journalism and the relations of music and literature. Nafiseh Mousavi holds a PhD in comparative literature and teaches intermedial studies at Lund University, Sweden. Her research focuses on the intersections of intermediality, migration, and memory practices. .